2015
DOI: 10.1167/iovs.14-16029
|View full text |Cite
|
Sign up to set email alerts
|

Blue Multifocal Pupillographic Objective Perimetry in Glaucoma

Abstract: In moderate to severe glaucoma, diagnostic accuracy of yellow and blue was similar, but blue stimuli showed limited ability to resolve scotomas. Blue mfPOP stimuli, however, may have advantages over yellow in detecting early glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 60 publications
2
61
0
Order By: Relevance
“…Previous reports of mfVEP responses from occipital electrodes in patients with T2D showed only significant implicit time delays in the absence of retinopathy; however those delays correlated poorly with regions of loss on mfERG27. Using mfPOP stimuli we have recently confirmed earlier literature2128 showing that the pupillary system can be substantially driven by the visual cortex29, especially when using the transient stimuli of mfPOP24. Given those findings, and the brain lesion studies indicting substantial involvement of the extra-striate cortex in pupillary responses of primates and humans2230, we here compare the mfVEP responses from electrodes covering the occipital cortex, and surrounding electrodes that are more biased to extra-striate cortex, for any sign of the hypersensitivities in the subjects from those two studies.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Previous reports of mfVEP responses from occipital electrodes in patients with T2D showed only significant implicit time delays in the absence of retinopathy; however those delays correlated poorly with regions of loss on mfERG27. Using mfPOP stimuli we have recently confirmed earlier literature2128 showing that the pupillary system can be substantially driven by the visual cortex29, especially when using the transient stimuli of mfPOP24. Given those findings, and the brain lesion studies indicting substantial involvement of the extra-striate cortex in pupillary responses of primates and humans2230, we here compare the mfVEP responses from electrodes covering the occipital cortex, and surrounding electrodes that are more biased to extra-striate cortex, for any sign of the hypersensitivities in the subjects from those two studies.…”
supporting
confidence: 81%
“…1B,C,D). Anatomically the pupillary system receives significant input from the extra-striate cortex21, and we have demonstrated cortical input to the responses obtained from the types of transient mfPOP stimuli used here2429. Thus it seems plausible that observed hypersensitivities in mfPOP derive from extra-striate input.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…18 Such interplay lays the foundation for the use of chromatic pupillometry as a tool to evaluate the integrity of visual functions and localize retinal dysfunctions in various ocular diseases, [19][20][21] including glaucoma. [22][23][24][25] Whether using direct or consensual pupillometry, 26,27 concomitantly with full-field, regional, or multifocal chromatic illumination paradigms, [22][23][24][25]27,28 previous studies have shown that the PLR, and particularly the intrinsic melanopsin-mediated postillumination pupillary response (PIPR), is altered in moderate and advanced stages of glaucoma. These pupillometric alterations correlate with structural (e.g., cup-to-disc ratio) and functional (e.g., VF mean deviation [VFMD]) defects across disease severities.…”
mentioning
confidence: 99%
“…9,[14][15][16][17][18][19][20][21][22][23] A different method of multifocal pupillographic perimetry (TrueField Analyzer; Tektronix, Beaverton, OR) uses white and colored stimuli analyzing both eyes simultaneously. [24][25][26] Although this technology is promising, it cannot differentiate between the rod and cone systems.…”
mentioning
confidence: 99%